Is an Artifact a Fact for the Art in Prehistory? - Naumov, Goce (Actual Problems of Theory and History of Art, 2017)
Archaeologists and many others involved in the humanities often use the term ‘artifact’ in order to refer objects produced in the past. Since its creation this term invokes a romantic image of such objects as works of art made by craftsmen, and comprises immense significance. Thus, artifacts are perceived as valued objects and the notion of art is embedded within their essence. But should we indeed understand artifacts as objects of art just because they were produced in the past? Many tools, pots, vehicles, books, buildings or household items made today are not considered art pieces, but when the same categories of objects are unearthed at archaeologicalsites they are named artifacts. Therefore the main question in this paper is: what are actually the criteria foran object modeled in past to be regarded as an artifact? Although it seems hard to find a convincing answer to such question, still the theoretical consensus should be obtained and, as a result, particular criteria for determination of an item as artifact should be worked out. In this case prehistoric finds will be primarily engaged in order to assert the differences and various levels of skills and contexts in producing and using ceramic and stone objects.